(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the role and importance of communicative competence in the development of students’ personal and professional qualities. It also highlights the pedagogical necessity of developing communicative competence in the modern educational process, discusses effective teaching methods, and examines the efficiency of communicative approaches and technologies in education.